Women Language Features Used By Female Judges And Female Contestants In Australian The Next Top Model Episode Session 10: Corpus Driven Approach - Daristin, Pipit Ertika; Setiawan, Slamet; Mustofa, Ali (International Journal for Educational and Vocational Studies, 2020)
This study was intended to describe women linguistic features used linguistic features used by female in different role, in this case is between judges and contestants in a television show, In Australian The Next Top Model, which show power and solidarity. The aims of this study are to find out what linguistic features of women used by female judges and female contestants in a competition show and to determine which role is more powerful and show more solidarity. It is shown that the female judges and the female contestants In Australian the Next Top Model Session 10 from episode 1 to 10 are on the two first features which are put on the most rank of used. Those features are lexical hedges and Intensifiers which have the highest frequency used of the female judges and the female contestants. And the other result that the elements of women’s language features influence the context found In Australian the Next Top Model Session 10 are Lexical Hedges or Filler, Empty Adjectives, Intensifiers, Avoidance of Strong Swear Word, Softening Remark and Acceptable Reason, Tag Question, and Super Polite For. The use of these language features depend on the context that is influenced by power and solidarity, dominant and inequality of the status uttered by the speaker of the female judges and the contestants. And then, total Women’s language features used by the female judges 162 while total Women’s language features used by Female contestants 327.